HANDBOOK kebijakan publik / editor Michael Maran, Martin Rein dan Robert E Goodin ; penerjemah Imam Baihaqie ; penyunting Rizal. - Maran, Michael; Rein, Martin; Goodin, Robert E.; Imam Baihaqie; Rizal (Nusa Media, 2015)
viii, 1199 hlm. ; 24 cm [3 eks.]